Family matters and readiness in disaster training: a descriptive qualitative study on nurses’ willingness to respond - Kimin, Amelia; Nurachmah, Elly; Putri, Arcellia Farosyah; Gayatri, Dewi; Lestari, Fatma; Afriyanti, Yati; Supartono, Basuki; Sujianto, Untung (Jurnal Ners, 2026)
Introduction: The increasing frequency and impact of disasters requires nurses to be adequately prepared and willing to respond. Previous studies have suggested that knowledge and skills alone are insufficient predictors of willingness to respond. This study aimed to explore factors influencing nurses’ willingness to respond to disasters beyond knowledge and skills and to identify strategies to enhance this willingness through disaster training. Methods: A qualitative descriptive study design was used. Data were collected from May to July 2020 through semi-structured interviews (n = 9) and focus group discussions (n = 10) involving nurses with earthquake response experiences in Indonesia. The participants were recruited using purposive and snowball sampling. Data were analyzed manually following Doyle’s qualitative descriptive approach to generate codes, categories, and themes. Results: Two major themes were identified: (1) dilemma in family matters, consisting of professional commitment, family safety, and family support; and (2) readiness to respond, including unprepared feelings and the role of disaster training. Family well-being emerged as a prerequisite for deployment, while realistic and simulation-based disaster training was perceived as essential for strengthening psychological readiness. Conclusions: Nurses’ willingness to respond to disasters is influenced not only by their knowledge and skills, but also by family related considerations and psychological preparedness. Disaster training programs should integrate family preparedness components and realistic simulation-based learning to enhance nurses’ readiness and willingness to respond effectively.